(untitled) (Bangladesh Journal of Zoology, 2016)
Induced breeding trial of two years old striped mullet (Mugil cephalus L.) was conducted during winter season in a commercial fish hatchery at Coxs Bazar, Bangladesh. Adult or sub-adults of M. cephalus were collected from the wild and reared in the saline ponds from August to December 2014. The broods were injected using carp PG, HCG and LRH-A2 after 48 hrs of acclimatization in the hatchery tanks. The effective doses of carp PG 30mg/kg body weight, LRH-A2150?g with a combination of 0.3ml Domperidone and 0.5 ml Calcium injection, and HCG dose of 30,000 IU in case of female and 5,000 IU in case of male were found to spawning success. The GSI value ranged between 7.92-12.38 and egg diameter of matured fish ranged between 563-594?m and that of fertilized egg between 650-680?m with fecundity calculated as 780 to 900 nos/g. The fish started spawning between 44-48 hrs and cell division was observed after the first hour of spawning, however, mass mortality occurred after 6 hrs of spawning. Bangladesh J. Zool. 43(2): 279-289, 2015